Regulation of Protein Binding Capability of Surfaces via Host-Guest Interactions Effects of Localized and Average Ligand Density - Shi, Xiujuan (Langmuir : the ACS journal of surfaces and colloids, 2015)
The protein binding capability of biomaterial surfaces can significantly affect subsequent biological responses, and appropriate ligand presentation is often required to guarantee the best functions. Herein, a new facile method for regulating this capability by varying the localized and average ligand density is presented. Binding between lysine and plasminogen relevant to a fibrinolysis system was chosen as a model. We integrated different lysine-modified β-cyclodextrin (β-CD) derivatives onto bioinert copolymer brushes via host-guest interactions. The localized and average lysine density can be conveniently modulated by changing the lysine valency on β-CD scaffolds and by diluting lysine-persubstituted β-CD with pure β-CD, respectively. Both the plasminogen adsorption and the plasminogen binding affinity were enhanced by lysine-persubstituted β-CD compared with those of lysine-monosubstituted β-CD, which is possibly due to the higher localized lysine density and the multivalent binding of plasminogen on lysine-persubstituted β-CD surfaces. With a change in the ratio of lysine-persubstituted β-CD to β-CD, the average lysine density can be tuned, leading to the linear regulation of the adsorption of plasminogen on surfaces